Existence of the 1x24 Hours Mandatory Reporting Guest Regulation in Order to Maintain Order and Peace in the Community Environment of Purbalingga Regency - Amanda Khaerunnisa (UM Purwokerto Press, 2023)
The Purbalingga Regency Government, in providing services regarding order, security, and tranquility, is regulated by Purbalingga Regency Regional Regulation Number 9 of 2016 concerning Public Order and Community Peace in Purbalingga Regency. In the process of upholding order and tranquillity in the community, the implementation of policies that have been made by the local government is a process of the stages of public service policy, especially regarding the policy of mandatory 1x24 hour reporting guest regulations whose targets are migrants from outside certain areas. However, the regulations do not openly explain the existence of these regulations, so this has led to many perceptions about the product of the policy rules. The purpose of this study is to implicate and analyse the 1x24 hour mandatory guest report regulation with Regional Regulation Number 9 of 2016 concerning Public Order and Community Peace in Purbalingga Regency. The method used in this research is descriptive qualitative method. The results of this study show that there is an interrelated relationship between the 1x24 hour mandatory guest report regulation and Regional Regulation Number 9 of 2016 concerning Public Order and Community Peace in Purbalingga Regency. Suggestions from the research results to the Purbalingga Regency Government as a basis for making legislation on public order that directly mentions the mandatory 1x24 hour guest report.